Natural history and patterns of treatment change in Parkinson's disease: A retrospective chart review. (2022) - Navaratnam, Prakash; Arcona, Steve; Friedman, Howard S.; Leoni, Matthew; Shaik, Shajahan; Sasane, Rahul
Highlights: PD management is complex and evolves as the disease progresses. Therapy dose escalations, switches, discontinuations, and add-ons are common. Relapses and adverse events are the most common reasons for therapy changes. Switches and dose escalations often occur within 6 months of initiation. Treatment in older patients is more cautious than in younger patients. Abstract: Background: Parkinson's disease (PD) management seeks to balance the benefits and harms of current medications and evolves as the disease progresses. The natural history of PD and associated patterns of treatment change were analyzed to identify unmet needs in treatment of PD symptoms. Methods: Medical charts of patients from clinics across the US diagnosed on or before June 30th, 2014 were retrospectively reviewed. Index date was the first clinic visit, and the post-index period was through study end (June 30th, 2019). Outcomes included the frequency of therapy changes in the post-index period, reasons for therapy change, and adverse events (AE). Results: Patients (n = 203) at index were receiving levodopa-peripheral dopa decarboxylase inhibitor (PDDI) monotherapy (47%), dopaminergic agonist (DA) monotherapy (15%), monoamine oxidase B inhibitor (MAOBI) monotherapy (14%), or combination therapies. The percentage of patients in Hoehn-Yahr disease Stage 1–2 was 52% at index and 20% by the end of the study. Frequencies of motor, non-motor, and neuropsychiatric symptoms increased during the enrollment. Levodopa-PDDI monotherapy and levodopa-PDDI + MAOBI had the lowest rates of therapy changes. Symptom relapse was the most common reason for dose escalation, add-on, and dose reduction, whereas AEs were the most common reason for discontinuation and switching. Dose escalation, add-on, and forward switch were most likely to occur in the first 6 months of treatment. Conclusions: Therapy changes during the study period reflected the challenging and evolving management of PD as the disease progresses. New or add-on symptomatic treatments are needed that are well-tolerated and able to control PD symptoms.